Analysis Of The E-Plantation System On Employee Performance Through Job Satisfaction at PT. Source Of Palm Mahardika - Afendi; Uripan, Koen Irianto; Sumunu, Trenggono; Soleha, Siti Nur; Zainuddin, Ahmad (International Humanity Advance, Business & Sciences, 2025)
This study aims to analyze the influence of the e-Plantation system on employee performance through job satisfaction at PT. Source of Palm Mahardika. In particular, this study examines three main aspects: (1) the effect of the e-Plantation system on job satisfaction, (2) the effect of job satisfaction on employee performance, and (3) the effect of the e-Plantation system on employee performance through job satisfaction. The population in this study is all employees of PT. Sumber Mahardika Sawit, which totals 45 people, with a working period of more than one year. Due to the limited population number, this study used a census method, in which the entire population was sampled. The data was analyzed using the Partial Least Squares (PLS) approach with the help of Smart PLS 3.0 software. The results of the study show that the e-Plantation system has a significant influence on employee job satisfaction, which in turn has a positive impact on employee performance. In addition, job satisfaction has been proven to be a mediating variable that strengthens the relationship between the e-Plantation system and employee performance. Thus, the optimal implementation of the e-Plantation system can increase job satisfaction, which will further contribute to improving overall employee performance.